The State-of-the-Art of Collaborative Technologies for Initial Vocational Education: A Systematic Literature Review - Schwendimann, Beat A.; De Wever, Bram; Hämäläinen, Raija; Cattaneo, Alberto A. P. (International Journal for Research in Vocational Education and Training, 2018)
Future workplaces require collaboration skills in which members of different work communities use technologies to solve complex problems. Vocational education and training (VET) programs need to meet the challenge to prepare students to be part of a competent workforce. Particularly initial vocational education is under pressure to develop learners’ collaboration skills and abilities. To date, however, no attempt has been made to perform a comprehensive review of the use of computer-supported collaborative learning (CSCL) technologies across different vocational education settings to account for contextual factors of VET. In this systematic review, 26 published studies were analyzed with respect to their demographics, research methodology, use of technology, and measured outcomes. This review illuminates that research on CSCL still leaves the vocational learning context as an under-represented field of study. At the same time, technologies offer a range of new types of learning possibilities for vocational education. As the direct result of that development, vocational education is increasingly taking place in new technology-enhanced learning settings. Education can benefit from the opportunities of CSCL technologies, but on the other hand, such technologies create new challenges for facilitating vocational learning. Therefore, this review also identifies three topic areas specific to vocational learning (collaborative writing-to-learn, simulations and game-like solutions, and tangible objects) and enumerates desirable lines for future research.